2020
DOI: 10.3390/mps3020039
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of DNA Extraction and Lipid Removal on Human Milk Bacterial Profiles

Abstract: Culture-independent molecular techniques have advanced the characterization of environmental and human samples including the human milk (HM) bacteriome. However, extraction of high-quality genomic DNA that is representative of the bacterial population in samples is crucial. Lipids removal from HM prior to DNA extraction is common practice, but this may influence the bacterial population detected. The objective of this study was to compare four commercial DNA extraction kits and lipid removal in relation to HM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 53 publications
(78 reference statements)
6
37
1
Order By: Relevance
“…Although kit NM recovered a significantly higher abundance of R. glycinis, this species was also found in the negative extraction control for this kit. The application of different DNA extraction methods resulted in variation in DNA yield and bacterial profiles, which is consistent with previous studies of HM (Douglas et al 2020;Ojo-Okunola et al 2020). Similarly, studies with other sample types have also reported variation in bacterial DNA profiles following DNA extraction with different kits (Yuan et al 2012;Wesolowska-Andersen et al 2014;Fouhy et al 2016;Glassing et al 2016;Hallmaier-Wacker et al 2018;Stinson et al 2018).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Although kit NM recovered a significantly higher abundance of R. glycinis, this species was also found in the negative extraction control for this kit. The application of different DNA extraction methods resulted in variation in DNA yield and bacterial profiles, which is consistent with previous studies of HM (Douglas et al 2020;Ojo-Okunola et al 2020). Similarly, studies with other sample types have also reported variation in bacterial DNA profiles following DNA extraction with different kits (Yuan et al 2012;Wesolowska-Andersen et al 2014;Fouhy et al 2016;Glassing et al 2016;Hallmaier-Wacker et al 2018;Stinson et al 2018).…”
Section: Discussionsupporting
confidence: 88%
“…This has important implications for the interpretation of data from previous studies. This results reported here, together with those reported previously in HM studies (Douglas et al 2020;Ojo-Okunola et al 2020), suggest that it is problematic to compare data from different HM microbiome studies that have utilized different extraction methods. Extraction efficiency is an important consideration for low-biomass samples.…”
Section: Discussionsupporting
confidence: 41%
See 3 more Smart Citations